The Indonesian Criminal Law System's Progression in Sexual Assaults Regulation - Endrianto Bayu Setiawan; Lintang Charahena Mustofa; Tia Rizki Febrianti; Luvieandra Pratama (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2022)
This article aims to analyze the development of the sexual assault regulation which comes from various sectoral acts in Indonesia. This research is a normative juridical research that uses primary legal materials in the form of laws and regulations and secondary legal materials in the form of legal books and legal articles. The analysis used is descriptive qualitative. The result of this study indicates that the massive cases of sexual assault that occur in private and public spaces have made it a serious crime that has to ben handled with approriate legal instruments. In Indonesia, sexual assault is a form of crime which its perpetrator can be convicted. Prior to the creation of The Sexual Assaults act Number 12 of 2022, the sexual assault regulation is already regulated in various separates acts. It caused disharmony of the regulation which implicates to non-optimal law enforcement. After the establishment of The Sexual Assaults act Number 12 of 2022, currently, Indonesia has a main legal protection in providing the handling, protection, and law enforcement of sexual assault. Since the passage of The Sexual Assaults act Number 12 of 2022, all the various separates acts have been regulated in a way that is more unified in a form of special law (lex specialis) which contains material and formal criminal arrangements.